An Analysis of Product Differentiation Strategies to Improve the Competitiveness of Culinary MSMEs: A Case Study of Ayam Geprek and Penyet Memei 2 - Alya Elmira Putri; Ana Teresia Br Girsang; Elya Br Barus; Kusmarini Kusmarini; Meli Yumita Sari; Ahmad Rifki (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the implementation of product differentiation strategies in enhancing the competitiveness of culinary micro, small, and medium enterprises (MSMEs), focusing on Ayam Geprek and Penyet Memei 2. This research employs a qualitative approach using a case study method to gain an in-depth understanding of the phenomenon. Data were collected through interviews, observations, and documentation involving business owners and consumers. The findings reveal that product differentiation is implemented through unique menu variations, distinctive flavors, and consistent product quality, which contribute to shaping positive consumer perceptions. In addition, the use of digital media such as social platforms supports marketing activities, although it has not been fully optimized. The study also identifies several operational challenges, including rising costs of supporting materials and limited managerial resources. Overall, the results indicate that product differentiation plays a significant role in strengthening business competitiveness. However, sustainable development requires continuous innovation, effective marketing strategies, and improved operational management to maintain long-term business viability.